Interactive segmentation for indoor scenes - Tai, C.; Liu, T.; Bagchi, J.; Zhu, Maggie; Allebach, J. (2017)
© 2017, Society for Imaging Science and Technology. We present a click-based interactive segmentation for indoor scenes, which allows the user to select an object or region within the scene in a few clicks. The goal for the click-based approach is to provide the user with a simple method to reduce the amount of input required for segmentation. We first present an effective global segmentation strategy, which provides a rough separation of different textures. The user, then, places a few clicks to segment the target. A novel Trimap assignment strategy is proposed to utilize the click information. To study the performance of our method, psychophysical experiments were conducted to compare our click-based approach with other existing methods.